Possibilities of radionuclide diagnostics of Her2-positive breast cancer using technetium-99m-labeled target molecules: the first experience of clinical use - O. D. Bragina; V. I. Chernov; E. Yu. Garbukov; A. V. Doroshenko; A. G. Vorobyeva; A. M. Orlova; V. M. Tolmachev (Бюллетень сибирской медицины, 2021)
Background. The main purpose of the Her2/neu status determination in clinical practice is to determine the indications for the appointment of targeted therapy. The main methods for detecting the Her2/neu status are the immunohistochemical method (IHC) and the fluorescence in situ hybridization (FISH); however, despite their widespread use, they have a number of significant disadvantages. Over the past few years, radionuclide diagnostics using a new class of alternative scaffold proteins that meet all the requirements for optimal delivery of radionuclides to tumor cells has become widespread.Aim. To study the possibility of clinical use of a radiopharmaceutical based on technetium-99m-labeled target molecules for the diagnosis of breast cancer with the Her2/neu overexpression in humans.Materials and methods. The study included 11 patients with breast cancer (T1–4N0–2M0) before systemic therapy: 5 with Her2/neu overexpression; expression of the marker was not detected in 6. In all cases, morphologicaland immunohistochemical studies were performed. In case of Her2/neu 2+, FISH analysis was performed. The radiopharmaceutical was prepared immediately before administration, after which it was slowly injected intravenously into the patient. Scintigraphic studies in the “WholeBody”  mode and SPECT of the chest organs were performed 2, 4, 6 and 24 hours after injection.Results. Radiochemical yield, radiochemical purity and activity before administration were (80 ± 4)%, (98 ± 1)% and (434 ± 19.5) MBq, respectively. The greatest uptake by normal organs was observed at a time interval of 6 hours in the kidneys and at a moderate activity in the liver and lungs at the same time interval. The organ with the highest absorbed dose was the  kidneys; significant accumulation was also detected in the adrenal glands,  gallbladder, liver, pancreas and spleen. The smallest accu mulation of the  studied drug was observed in the brain (0.001 ± 0.000) mGy and skin (0.001  ± 0.000) mGy. The effective dose was (0.009 ± 0.002) mGy. The difference between tumors with positive and negative Her2-neu expression was found at all time points. In this case, the best indicator was determined after 2 hours of drug injection (р < 0.05).Conclusion. Based on the results obtained, it can be indicated that the investigated radiopharmaceutical can be considered as a new additional method for the diagnosis of Her2-positive breast tumors.